Impaired receptivity of thin endometrium: therapeutic potential of mesenchymal stem cells - Saad-Naguib, Michael H.; Kenfack, Yannick; Sherman, Lauren S.; Chafitz, Olivia B.; Morelli, Sara S. (Frontiers in Endocrinology, 2024)
The endometrium is a resilient and highly dynamic tissue, undergoing cyclic renewal in preparation for embryo implantation. Cyclic endometrial regeneration depends on the intact function of several cell types, including parenchymal, endothelial, and immune cells, as well as adult stem cells that can arise from endometrial or extrauterine sources. The ability of the endometrium to undergo rapid, repeated regeneration without scarring is unique to this tissue. However, if this tissue renewal process is disrupted or dysfunctional, women may present clinically with infertility due to endometrial scarring or persistent atrophic/thin endometrium. Such disorders are rate-limiting in the treatment of female infertility and in the success of in vitro fertilization, because of a dearth of treatment options specifically targeting the endometrium.A growing number of studies have explored the potential of adult stem cells, including mesenchymal stem cells (MSCs), to treat women with disorders of endometrial regeneration.MSCs are multipotent adult stem cells with capacity to differentiate into cells such as adipocytes, chondrocytes, and osteoblasts. In addition to their differentiation capacity, MSCs migrate towards injured sites where they secrete bioactive factors (e.g. cytokines, chemokines, growth factors, proteins and extracellular vesicles) to aid in tissue repair. These factors modulate biological processes critical for tissue regeneration, such as angiogenesis, cell migration and immunomodulation. The MSC secretome has therefore attracted significant attention for its therapeutic potential. In the uterus, studies utilizing rodent models and limited human trials have shown a potential benefit of MSCs and the MSC secretome in treatment of endometrial infertility.This review will explore the potential of MSCs to treat women with impaired endometrial receptivity due to a thin endometrium or endometrial scarring. We will provide context supporting leveraging MSCs for this purpose, by including a review of mechanisms by which the MSC secretome promotes regeneration and repair of nonreproductive tissues.